Existing feeding practices and production performance of lactating buffaloes in selected agro-climatic zones of Bangladesh - Rahman, SMR; Islam, MN; Rashid, MH; Sarker, NR; Siddiki, MSR; Bari, MS; Islam, MA (Bangladesh Journal of Animal Science, 2020)
A study was conducted to observe the existing feeding practices, nutritional supply and production performance of the lactating buffaloes in some selected agro-climatic zones of Bangladesh, viz. Bhola (AEZ-18, Coastal area), Mymensingh (AEZ-22, River basin area) and Dinajpur (AEZ-27, Drought area). Data on availability, amount and types of feeds and fodders fed to the lactating buffaloes, body weight, milk yield and quality and lactation length were collected from 30 farmers of the each selected locations. In this investigation, the mostly used feed ingredients found were rice straw, locally available green grasses, wheat bran, broken maize, mustard oil cake and broken rice. Total feed supply (DM kg/h/d) to lactating buffaloes were 17.4, 14.5 and 13.0 in coastal, river basin and drought areas, respectively, (p>0.05). But significantly (p = 0.000) different amount (DM kg/h/d) of concentrate were supplied in coastal (1.5), river basin (1.8) and drought (2.7) areas. The highest amount (kg/h/d) of green grass was supplied in coastal area (5.0) followed by river basin area (4.3) and drought area (1.3). Accordingly, amount (kg/d) of DCP and TDN were supplied was higher in coastal area (0.365 and 6.417, respectively) than that of the river basin and drought areas (0.247-0.248 and 5.501-5.891, respectively), which were below their requirements. Significantly (p=0.000) larger lactating buffaloes were found in the river basin and drought areas (weighed 372–380 kg/h) than that of coastal area (242 kg/h). The average daily milk yield was found significantly highest (p=0.000) in the drought area (5.3 L/d) which was 1.4 L and 3.1L more than that of the river basin and coastal area, respectively. The 4% FCM yield was found two times more (p=0.000) in drought area (7.7 kg/d) than that of the coastal (3.1 kg/d) and river basin (3.6 kg/d) area. On the other hand, the significantly (p=0.000) highest lactation length and lactation yield were 294 d and 1085 L, in the river basin area, which were 189 d and 1007 L in drought area and 197d and 429 L in coastal area, respectively. Among the milk constituents, protein, ash and lactose content was found higher in drought area than that of the other two areas (p=0.001). In conclusion, the prevailing variations are evidently considerable. Therefore, suggesting further works for large scale baseline data regarding buffalo populations, nutritive quality of feeds and fodder, effectiveness of existing management tools and adoption of new technologies. Bang. J. Anim. Sci. 2019. 48 (2): 127-138